Nine-year change in statistical design, profile, and success rates of Phase II oncology trials. Issue 1 (2nd January 2016) - Ivanova, Anastasia; Paul, Barry; Marchenko, Olga; Song, Guochen; Patel, Neerali; Moschos, Stergios J.
ABSTRACT: We investigated nine-year trends in statistical design and other features of Phase II oncology clinical trials published in 2005, 2010, and 2014 in five leading oncology journals : Cancer, Clinical Cancer Research, Journal of Clinical Oncology, Annals of Oncology, and Lancet Oncology. The features analyzed included cancer type, multicenter vs. single-institution, statistical design, primary endpoint, number of treatment arms, number of patients per treatment arm, whether or not statistical methods were well described, whether the drug was found effective based on rigorous statistical testing of the null hypothesis, and whether the drug was recommended for future studies .